BAC Library of T. pallidum DNA in E. coli - Šmajs, David (Cold Spring Harbor Laboratory Press, 2002)
Treponema pallidum subspecies pallidum (Nichols) chromosomal DNA was used to construct a large insert bacterial artificial chromosome (BAC) library in Escherichia coli DH10B using the pBeloBAC11 cloning vector; 678 individual insert termini of 339 BAC clones (13.9 x coverage) were sequenced and the cloned chromosomal region in each clone was determined by comparison to the genomic sequence. A single 15.6-kb region of the T. pallidum chromosome was missing in the BAC library, between bp 248727 and 264323. In addition to the 12 open reading frames (ORFs) coded by this region, one additional ORF (TP0596) was not cloned as an intact gene. Altogether, 13 predicted T. pallidum ORFs (1.25% of the total) were incomplete or missing in the library. Three of 338 clones mapped by restriction enzyme digestion had detectable deletions and one clone had a detectable insertion within the insert. Of mapped clones, 19 were selected to represent the minimal set of E. coli BAC clones covering 1026 of the total 1040 (98.7%) predicted T. pallidum ORFs. Using this minimal set of clones, at least 12 T. pallidum proteins were shown to react with pooled sera from rabbits immunized with T. pallidum, indicating that at least some T. pallidum genes are transcribed and expressed in E. coli.